Defining specific residue‐to‐residue interactions between the gp120 bridging sheet and the N‐terminal segment of CCR5: applications of transferred NOE NMR. (20th October 2018) - Srivastava, Gautam; Moseri, Adi; Kessler, Naama; Arshava, Boris; Naider, Fred; Anglister, Jacob
Abstract : Infection by HIV‐1 requires protein–protein interactions involving gp120, CD4 and CCR5. We have previously demonstrated that the transferred nuclear Overhauser effect (TRNOE), in combination with asymmetric deuteration of a protein and a peptide ligand can be used to detect intermolecular interactions in large protein complexes with molecular weights up to 100 kDa. Here, using this approach, we reveal interactions between tyrosine residues of a 27‐residue peptide corresponding to the N‐terminal segment of the CCR5 chemokine receptor, and a dimeric extended core YU 2 gp120 envelope protein of HIV‐1 complexed with a CD4‐mimic miniprotein. The TRNOE crosspeaks in the ternary complex were assigned to the specific Tyr protons in the CCR5 peptide and to methyl protons of isoleucine, leucine and/or valine residues of gp120. Site directed mutagenesis combined with selective deuteration and TRNOE resulted in the first discernment by a biophysical method of specific pairwise interactions between gp120 residues in the bridging sheet of gp120 and the N‐terminus of CCR5. Abstract : A surface representation of the gp120 bridging sheet indicating in red residues that interact with aromatic residues in the N‐terminus of the chemokine receptor CCR5 (Nt‐CCR5). Specific pairwise interactions involving these residues were determined, using TRNOE, selective deuteration and site directed mutagenesis on a gp120/CD4 mimic/Nt‐CCR5 complex.